Mitochondrial Oxidative Metabolism: An Emerging Therapeutic Target to Improve CKD Outcomes - Kranti A. Mapuskar; Gabriela Vasquez-Martinez; Gabriel Mayoral-Andrade; Ann Tomanek-Chalkley; Diana Zepeda-Orozco; Bryan G. Allen (Biomedicines, 2023)
Chronic kidney disease (CKD) predisposes one toward end-stage renal disease (ESRD) and its associated morbidity and mortality. Significant metabolic perturbations in conjunction with alterations in redox status during CKD may induce increased production of reactive oxygen species (ROS), including superoxide (O2●−) and hydrogen peroxide (H2O2). Increased O2●− and H2O2 may contribute to the overall progression of renal injury as well as catalyze the onset of comorbidities. In this review, we discuss the role of mitochondrial oxidative metabolism in the pathology of CKD and the recent developments in treating CKD progression specifically targeted to the mitochondria. Recently published results from a Phase 2b clinical trial by our group as well as recently released data from a ROMAN: Phase 3 trial (NCT03689712) suggest avasopasem manganese (AVA) may protect kidneys from cisplatin-induced CKD. Several antioxidants are under investigation to protect normal tissues from cancer-therapy-associated injury. Although many of these antioxidants demonstrate efficacy in pre-clinical models, clinically relevant novel compounds that reduce the severity of AKI and delay the progression to CKD are needed to reduce the burden of kidney disease. In this review, we focus on the various metabolic pathways in the kidney, discuss the role of mitochondrial metabolism in kidney disease, and the general involvement of mitochondrial oxidative metabolism in CKD progression. Furthermore, we present up-to-date literature on utilizing targets of mitochondrial metabolism to delay the pathology of CKD in pre-clinical and clinical models. Finally, we discuss the current clinical trials that target the mitochondria that could potentially be instrumental in advancing the clinical exploration and prevention of CKD.